The Warren Buffett way : investment strategies of the world's greatest investor - Hagstrom, Robert G. (New York : J. Wiley, 1994)
The Warren Buffett Way offers investors their first in-depth look at the innovative investment and business strategies behind the spectacular success of living legend Warren E. Buffett. Tracing Warren Buffett's career from the beginning, Robert G. Hagstrom, Jr., tells us exactly how, starting with an initial investment of only $100, Buffett built a business empire worth $19.4 billion. Offers a close-up look at Buffett's highly successful investment theories and strategies; identifies the types of businesses Buffett now finds most attractive, and which ones he avoids; and based on the author's ten-year monitoring of Buffett's numerous shrewd investments and ventures.
Includes bibliographical references and index.
Keywords: Capitalists and financiers -- United States -- Biography